Festivais da canção: uma proposta de leitura - Silva, Anaiza Rodrigues da (2012)
The song festivals held in Brazil between 1965 and 1985, became a historical, cultural and political landmark of our country, considered today as one of the most creative moments of our popular music. They revealed great MPB talents and brought to light beautiful compositions that boldly defied the rules imposed by the military government. During the military dictatorship, censorship acted strongly against all forms of communication and cultural expression, especially music. Artists were imprisoned, tortured, exiled. Compositions were banned or had their lyrics changed so they could go public. Despite censorship and repressive means used by the military government, many composers do not shut up and continued to convey, through music, their message of protest. To be able to say what they wanted, but could not, these composers have relied on language resources that deserve to be studied. Through implicit contents these songs could pass the scrutiny of censorship and, while carrying the message to the public, who learned to read between the lines. We seek with this research demonstrate which language resources which enabled the implicit assumptions and implied and specifically how they are identifiable in the text. We found that to understand the implied collaborate factors beyond the structural aspect of language. In this sense, besides the marks highlighted in the text, contribute the context of enunciation, the intertext, the encyclopedic knowledge, the reader's expectations. We conclude that the implicit feature was much explored by composers since the creation of meaning to content implicit is the responsibility of the reader, allowing the enunciator deny responsibility for what was said